(untitled) (Scientia Agricola, 2013)
Mandarins have become increasingly valued as citrus fruits for the fresh market due to the easy peeling, attractive flavor, and health and nutritional properties. Plant growth and yield, and characteristics of fruits of 'Okitsu' Satsuma mandarin (Citrus unshiu Marc.) trees grafted on nine rootstocks were evaluated in Londrina, northern Paraná, Brazil. The rootstocks were: 'Rangpur' lime (Citrus limonia Osb.); 'Cleopatra' (Citrus reshni hort. ex Tanaka) and 'Sunki' mandarins (Citrus sunki hort. ex Tanaka); 'C-13' [Citrus sinensis × Poncirus trifoliata (L.) Raf.] and 'Carrizo' citranges [C. sinensis × P. trifoliata (L.) Raf.]; 'Volkamer' lemon (Citrus volkameriana V. Ten. & Pasq.); trifoliate orange [P. trifoliata (L.) Raf.; 'Caipira DAC' sweet orange [C. sinensis (L.) Osb.] and 'Swingle' citrumelo [Citrus paradisi Macfad. cv. Duncan × P. trifoliata (L.) Raf.]. The highest plant growth was for the trees on 'Cleopatra' mandarin and 'Caipira DAC' sweet orange. In contrast, the smallest size was for the trees on 'Volkamer' lemon and trifoliate orange. The largest difference between the trunk diameter below and above the grafting point was induced by 'Swingle' citrumelo. Trees of 'Okitsu' Satsuma mandarin on 'Swingle' citrumelo presented the highest yield, while 'C-13', 'Carrizo', 'Sunki', and 'Swingle' induced the largest fruit masses. With regard to fruit characteristics, 'Carrizo' and trifoliate orange induced the best ratio and juice content. Based on theoretical values, 'Rangpur' lime and 'Volkamer' lemon induced the lowest yields